Launch workshop: Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns - Southeast Asian Regional Center for Graduate Study and Research in Agriculture (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2021)
SEARCA Headquarters, Los Baños, Laguna, Philippines. The International Food Policy Research Institute (IFPRI) and the Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA) jointly organized the launch workshop of the project Agricultural Transformation and Market Integration in the ASEAN Region: Responding to Food Security and Inclusiveness Concerns on 7-8 October 2016. More than 50 experts from international organizations, government agencies, academic institutions, civil society, and the private sector representing Cambodia, Lao PDR, Myanmar, the Philippines, Vietnam, China, India, the United States of America, and Italy took part in the discourse on global, regional, and national perspectives on agricultural transformation and market integration in the ASEAN region.